Do rainfall shocks prompt commercial input purchases amongst smallholder farmers in diverse regions and environments in Malawi? - Makate, Clifton; Makate, Marshall (MDPI AG, 2022)
The ability of farmers to acquire inputs through purchase from available markets empowers them with the autonomy and capacity to diversify inputs, consequently enhancing the resilience of their cropping activities to various shocks. This paper investigates whether climate shocks, particularly rainfall shocks, influence commercial input purchase decisions by smallholder farmers in contrasting geographic regions in Malawi, with a particular emphasis on fertilizer, agrochemicals, seed, and labor. The empirical approach integrates historical weather information, climate shock perceptions with a longitudinal household survey data set to model commercial input purchasing decisions using appropriate latent variable models. The findings suggest that exposure to recent rainfall shocks, especially droughts, stimulates commercial input purchasing across regions, especially in drier central and southern regions of Malawi. This result holds true for general input purchase decisions and for specific inputs such as agrochemicals, fertilizer, seed, and labor. Although drought shocks considerably increase the probability of acquiring inputs through purchase, they occasionally diminish the intensity of purchases. Both objective and subjective measures of lagged rainfall shocks are revealed as significant determinants of commercial input purchases across regions in Malawi. In addition to regional heterogeneity findings, further analysis shows that the relatively wealthier, male-headed families and those with access to information are more likely to invest in purchased inputs in response to drought shocks. Scaling up policies that remove demand- and supply-side barriers to smallholder farmers’ access to commercial inputs from available markets is necessary for adaptation to rainfall shocks.